ANALYSIS OF THE IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT AT THE SOE REGIONAL PUBLIC HOSPITAL (RSUD) - Semei Elbot Fallo; Apriana H.J Fanggidae; Rolland E. Fanggidae (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The increasing public demand for quality hospital services necessitates the implementation of Total Quality Management (TQM) to continuously improve service quality. This study aims to analyze the implementation of TQM and identify supporting and inhibiting factors at Soe Regional General Hospital (RSUD Soe). The research method used was descriptive qualitative, with data collection techniques through interviews, observation, and documentation, as well as analysis using triangulation and SWOT analysis. The results indicate that the implementation of TQM at Soe Regional General Hospital is ongoing but not yet optimal, as indicated by the existence of Standard Operating Procedures (SOPs), a focus on patients, and leadership commitment. However, obstacles remain, such as limited human resources, especially specialist doctors, lack of training, inadequate facilities, and low service efficiency. The study concludes that the implementation of TQM needs to be improved through strengthening human resources, improving facilities, increasing adherence to SOPs, and optimizing the service system to achieve better service quality.